Thematic Analysis on the Integration of Engineering Concepts in Physical Education: A Collective Approach for Innovative Transformation - Ajithkumar L; Kumar P; Parveen Kumar; Kasthuri Thilagam P (CV Media Inti Teknologi, 2024)
This study explores integrating engineering concepts into the physical education (PE) curriculum, aiming to develop student experiences and progressive development. The objectives include exploring benefits associated with incorporating engineering principles, including preventing injuries through movement analysis and biomechanics, stimulating creativity and problem-solving skills with sports equipment, and strengthening theoretical knowledge through practical experiences in designing fitness equipment. The methods involved a comprehensive approach by literature reviews. The observed benefits include enhanced problem-solving abilities, improved creativity, and the practical application of theoretical knowledge, all contributing to a good educational experience. This interdisciplinary approach not only prepares students for a technologically advanced society but also ongoing research, collaboration, and implementation to maximize its educational potential in both physical education and engineering.